Moznosti vyuzitia digitálneho zobrazovania v súdnom lekárstve - Gaval'a, P; Ivicsics, I; Mlynár, J; Novomeský, F (Soudni lekarstvi, 2005)
Based on the daily practice with digital photography and documentation, the authors point out the achievements of the computer technologies implementation to the practice of forensic medicine. The modern methods of imaging, especially the digital photography, offer a wide spectrum of use in forensic medicine--the digital documentation and archivation of autopsy findings, the possibility of immediate consultation of findings with another experts via Internet, and many others. Another possibility is a creation of digital photographic atlas of forensic medicine as a useful aid in pre- and postgradual study. Thus the application of the state-of-the-art computer technologies to the forensic medicine discloses the unknown before possibilities for further development of such a discipline of human medical sciences.
Keywords: soudní lékařství; Medical Informatics; lékařská informatika; Photography; lidé; Autopsy; fotografování; pitva; Forensic Medicine; Humans